COMPARISON of Chinese and Foreign Specifications on Bending Behavior of Z-Purlins under Wind Uplift Load. Issue 1 (June 2020) - Huang, Rui; Luan, Wei
Abstract: It is very difficult to calculate the bending bearing capacity of cold-formed purlins under wind uplift load precisely. The design requirements, which are different in Chinese and foreign specifications, such as GB 50018, CECS 102, EN 1993-1-3, AISI S100 and AS/NZS 4600, are summarized comprehensively. The differences of design methods, calculation models and considerations on restraint effects of lightweight steel roof systems among these specifications are also discussed. The bending bearing capacity of 18 rows of commonly used Z-purlins calculated according to these specifications is analyzed. The analysis shows that for purlins without sag-rod, the calculation results of GB50018 are conservative because the beneficial effects of restraint from lightweight steel roof systems are neglected. For purlins with two rows of sag-rods per span, the calculation results of GB50018 are nearly 20% greater than that of EC3, and the results of AS/NZS are the largest.